Primary teachers’ readiness to use project: investigate teachers’ efficacy and attitude toward project-based learning - Ariyani, Yusinta Dwi; Wilujeng, Insih; Wangid, Muhammad Nur; Wijaya, Dhina Puspasari; Wahyudi, Andi; Istiqomah, Istiqomah (Institute of Advanced Engineering and Science, 2024)
The purpose of our study was to investigate primary teachers’ readiness to use project-based learning (PBL) using teachers’ efficacy and teachers’ attitude toward PBL. A correlational descriptive design was set as the research design on 109 primary teachers from various schools who had participated in collaborative work projects in 2023. To collect data, teachers’ efficacy and teachers’ attitude scale were used as instrument. The results found that the level of use of PBL was influenced by teachers’ attitude toward PBL for each subscale except on the knowledge dependence and system restriction. The study also found that the level of use of PBL has a positive relationship with each subscale of teachers’ efficacy and the level of teachers’ efficacy is influenced by teachers’ attitude toward PBL for each subscale, except for the knowledge dependence. Implications of this study are expected to be considerations for professional development that focus on more concrete practical training.